Screening and Production of Antibacterial from Lactobacillus plantarum NS(9) Isolated from Nile Tilapia Bekasam - Desniar Desniar; Iriani Setyaningsih; Yoga Indra Purnama (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Lactic acid bacteria has been used as biopreservatif becouse produce a number of antibacterialsubstances are safety and has inhibitory activity against enteropatogenic bacteria. The aims of this studywere to screen of antibacterial compounds produced by Lactobacillus plantarum NS (9) and to producetheir antibacterial compounds. The research was devided into two stages. In the first stage was L. plantarumNS (9) inoculated at 37°C, for 24 hours in semi-anaerobic conditions. The cell-free supertnatant was giventhree treatment, ie not neutralized (A), neutralized (pH 7) (N), and precipitated with ammonium sulfate50% (P). This three supernatant was assayed their antibacterial activity against E. coli, S. typhimuriumATCC 14028, S. aureus, B. cereus and L. monocytogenes using the agar well diffusion method. In the secondstage, production of antibacterial compound was L. plantarum NS (9) inoculated at 37°C, for 24 hoursin semi-anaerobic conditions. The Dencity Optical, value pH, acid total and antibacterial activity weremeasured every three hours during growth of bacteria. The results of the antibacterial screening showedthat L. plantarum NS (9) produced inhibitory zone againts the five indicator bacteria from a supernatant,whereas N and P supernatant were not produced inhibitory zone. This result indicated that inhibition.produced at 6 hours of incubation and were increased to simultaneously with increasing of bacteria growth.The highest antibacterial activity against E. coli, B. cereus and L.monocytogenes were produced at the endof the exponential growth phase (12 -15 hours incubation) while against S. aureus and S. typhimuriumATCC 14028 at 21 and 24 hour of incubation, respectively. The antibacterial activity also was increased tosimultaniously with increasing of acid total (1.350 to 4.050%) and decreasing of pH value (6-4) duringgrowth of bacteria.